ANALISIS KINERJA PORTOFOLIO OPTIMAL CAPITAL ASSET PRICING MODEL (CAPM) DAN MODEL BLACK LITTERMAN - Anton Suhartono; Sugito Sugito; Rita Rahmawati (Jurnal Gaussian, 2015)
Stock portfolio is investment which comprised of various stocks from different companies, with the hope when the price of one stock decreases, while the other increases, investments do not suffer losses.The final stage in the investment process is to assess the performance of a portfolio. The purpose of portfolio performance assessment is to determine and analyze whether the formed portfolio have a better performance than other portfolios. Capital Asset Pricing Model (CAPM) explains that historical data and unrisk asset are used to to form portfolio. Black Litterman modelis developed by Robert Litterman and Fisher Black in the 1990s, forming a portfolio by combining historical data and investor intuition or investor views about the economic conditions that are happening. CAPM portfolio and Black Litterman model portfolio performance assessment can be performed by using Sharpe index, Treynor index and Jensen index. This research uses data from closing prices of stocks that join BISNIS-27 Index on period January 2010 until December 2014. Based on Sharpe index, Treynor index and Jensen index, optimal portfolio is CAPM portfolio with consisted by two stocks and the proportion investement are 86.936% for BMRI and 13.064% for INCO. Keywords: BISNIS-27 Index, Portfolio, Capital Asset Pricing Model (CAPM), Black Litterman Model, Treynor Index, Sharpe Index, Jensen Index.